The Management System Review of The Traditional Health Service Program in Public Health Centers - Vinelda Mathilda Wetangterah; Tadeus A. L. Regaletha; Daniela L. A. Boeky (Lontar : Journal of Community Health, 2020)
Kupang City has trained traditional health service program managers in 11 public health centers, but they have not implemented traditional health service programs properly. Implementation of traditional health service programs at the public health center is only limited to collecting data on traditional healers and the Independent Care Group (ASMAN) on the use of TOGA and acupressure that already exist in the community. This study is descriptive qualitative that aims to determine the description of program implementation from the aspects of input, process, and output. This study used a purposive sampling technique and the informants are 11 managers of traditional health service programs at 11 public health centers. The results showed limited funding is one of the reasons for not reaching health service coverage in Kupang City. The traditional health services of the public health center program manager in Kupang City have been trained and are adequate both in terms of the number and quality of human resources. The planning process was carried out starting from the public health center level, then discussed at the Kupang City Health Office level, but not all planning could be accommodated. This condition depicts that traditional health care has a huge potential and needs enough attention as a part of national health development. Many factors deploy the reaching of fund target, trained health workers, and data-based planning which is not fulfilled yet. It is hoped that the health office both in the city and province can provide guidance and supervision of all public health centers.